1993
DOI: 10.1093/oxfordjournals.humrep.a138121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epidermal growth factor in the final stages of nuclear and cytoplasmic oocyte maturation in humans

Abstract: Evidence has accumulated in mammals suggesting a positive role for epidermal growth factor (EGF) as an inducer of oocyte maturation. The potential use of EGF as inducer of cytoplasmic and nuclear maturation was tested in women with > 10 oocytes retrieved in in-vitro fertilization (IVF), since we have previously observed that such oocytes are immature. Oocytes from 17 high responders were randomly allocated to one of the three treatment groups upon retrieval: control receiving no EGF (n = 93), 1.0 ng/ml EGF (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Whether these factors promote the nuclear maturation via their direct effects on the oocyte, or via the coronal cells, also expressing EGF, EGF receptors and IGF receptors (Maruo et al, 1993) is not known. However, fertilization or resulting embryo quality was not enhanced when human oocytes were fertilized in the presence of EGF (Gómez et al, 1993b).…”
Section: Proposed Intrafollicular Triggers Of Oocyte Nuclear Maturationmentioning
confidence: 92%
“…Whether these factors promote the nuclear maturation via their direct effects on the oocyte, or via the coronal cells, also expressing EGF, EGF receptors and IGF receptors (Maruo et al, 1993) is not known. However, fertilization or resulting embryo quality was not enhanced when human oocytes were fertilized in the presence of EGF (Gómez et al, 1993b).…”
Section: Proposed Intrafollicular Triggers Of Oocyte Nuclear Maturationmentioning
confidence: 92%
“…Thus, EGF may not play a major role in hCG signal transduction, at least in human beings. G omez et al (32) reported that EGF, when added to culture media before insemination, had no positive effects on either the FR or blastomere development of human oocyte. This is consistent with our finding of scant EGF in FF.…”
Section: Figurementioning
confidence: 99%
“…Luteinizing hormone, and thus presumably hCG, can stimulate granulosa cells of antral follicles to produce EGF-like factors [7], and theca cells to produce insulin-like growth factors [37]. These factors are known to influence oocyte cytoplasmic maturation [38,39] which may translate into effects on subsequent embryonic developmental competence. Based on DNA microarray analyses of ovarian genes during the preovulatory period, Kawamura and colleagues [40] have found major increases in BDNF (brain-derived neurotrophic factor) expression after LH or hCG stimulation.…”
Section: Discussionmentioning
confidence: 99%